2020
DOI: 10.3892/ol.2020.11938
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal dexmedetomidine combined with local anesthesia for conscious sedation during breast lumpectomy: A prospective randomized trial

Abstract: Breast lumpectomy is usually performed under general or local anesthesia. To the best of our knowledge, whether conscious sedation with intranasal dexmedetomidine and local anesthesia is an effective anesthetic technique has not been studied. Thus, the present study aimed to investigate the effectiveness of conscious sedation with intranasal dexmedetomidine combined with local anesthesia in breast lumpectomy, and to identify its optimal dose. A prospective randomized, double-blinded, placebo-controlled, single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 39 publications
(65 reference statements)
0
8
2
Order By: Relevance
“…We found that dosages of 0.8 and 1.0 µg/kg reduce uterine contractions and extend the rst stage of labor. This result was inconsistent with the report in a previous study [22]. The rst reason was that most of the subjects were children who have different pharmacokinetics and apparent volumes of distribution than older subjects.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…We found that dosages of 0.8 and 1.0 µg/kg reduce uterine contractions and extend the rst stage of labor. This result was inconsistent with the report in a previous study [22]. The rst reason was that most of the subjects were children who have different pharmacokinetics and apparent volumes of distribution than older subjects.…”
Section: Discussioncontrasting
confidence: 80%
“…DEX induces cooperative and conscious analgesia and sedation, modulates the release of catecholamines and relieves maternal anxiety. YUAN et al showed that IND combined with local anesthesia resulted in conscious analgesia, sedation and improved anesthetic effects during breast lumpectomy [22]. Here, IND was used to relieve maternal anxiety and didn't affect cooperation during delivery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While DEX is mainly utilized in intensive care units due to its demonstrated suitability for achieving both short- and longer term sedation [ 1 , 2 ], it has more recently been applied in conjunction with local anesthesia in various surgical fields due to its minimal effects on respiratory depression. Several studies have noted that incorporating DEX into the regimen can induce light intraoperative sedation, which can help alleviate the fear of surgery in patients undergoing ophthalmological procedures [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%